Artificial Intelligence In Marketing - Sadok ,Achour; Ayadi ,Salah (جامعة الوادي University of Eloued, 2025)
This research examines the transformative role of artificial intelligence (AI) in marketing, addressing its potential to enhance organizational efficiency, boost customer engagement, and improve business outcomes. The study aims to explore innovative AI applications, such as big data analytics and deep learning, to enable precise decision-making and personalized marketing campaigns. The findings reveal that AI significantly improves campaign personalization and customer satisfaction, leading to increased sales and loyalty. However, challenges such as skill gaps, privacy concerns, and organizational resistance persist. The study recommends enhancing technical training and implementing ethical strategies to overcome these barriers and ensure sustainable success in digital markets.
Artificial Intelligence in Marketing: A Strategic Tool for Enhancing Business Growth
Keywords: Artificial Intelligence; Marketing; Business; Strategic Tools; Customer Engagement; Innovation